Differences In the Effectiveness of Online Learning Methods Compared to Offline Learning (A Case Study of Accounting Students from the 2018-2019 Batch, Faculty of Business Economics, Universitas Brawijaya) - Daffa, Adhitya; Djamhuri, Ali (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
The Coronavirus (COVID-19) officially announced as a severely infectious virus by the World Health Organization (WHO) in 2019-2020 made the Indonesian government implement physical distancing and social distancing, if not all large-scale social restrictions or PSBB. As such, during the pandemic, the learning process were no longer conducted on-site, instead, must be conducted online. This study aims to determine whether on-site learning is more effective than online one, based on Learning Theory. The population includes 597 accounting students of Faculty of Economics and Business of Universitas Brawijaya, the academic year of 2018-2019, from which the samples 34 respondents are selected through a simple random sampling technique. Data are collected through survey using questionnaires distributed through social media to all students, and analyzed by a Likert scale utilizing t-test statistical test. This study suggests that on-site learning method is proved to be more effective for the students than online learning. The results of this study can be used to determine the preference of future educational methods.